Opioid-Free Anesthesia: Current Evidence, Clinical Applications, and Future Perspectives - Rialta Hamda; Rahma Yulia Putri; Annisa Lidra Maribeth (CV. AKBAR PUTRA MANDIRI, 2026)
Background: Opioid-Free Anesthesia (OFA) has emerged as a revolutionary paradigm utilizing non-opioid multimodal analgesia to achieve stable nociceptive control without intraoperative opioids. This review evaluates the clinical evidence, practical applications, and implementation challenges of OFA. Methods: A comprehensive literature review was conducted across PubMed, ScienceDirect, and Google Scholar, selecting randomized controlled trials (RCTs) from the last five years. Data extracted included study designs, surgical typologies, pharmacological regimens, and clinical outcomes. Results: OFA provides non-inferior intraoperative stability and analgesia while significantly enhancing recovery scores, sleep quality, and PONV reduction. However, its efficacy is surgical-specific: it markedly reduces morphine needs in visceral procedures (bariatric/colorectal) but offers no advantage over optimized opioid-sparing anesthesia in musculoskeletal surgeries like total hip arthroplasty. Furthermore, high-dose non-opioid adjuncts introduce challenges like prolonged extubation, increased PACU stay, and sympathetic fluctuations. Conclusion: OFA is a safe and effective technique that minimizes opioid-related complications and improves recovery, particularly for high-risk patients and oncological surgeries. However, its benefits are surgical-specific and not universally superior to optimized Opioid-Sparing Anesthesia (OSA). Future universal adoption requires standardized dosing and objective monitoring (pEEG and Surgical Pleth Index) to ensure predictable recovery.